Lope entre voz y silencio: notas sobre teatralización y dramaturgia en la España de la temprana edad moderna - Kiss, Tamás Zoltán (Acta Hispanica, 2012)
The principal goal of this essay is to deliver study materials for the interpretation of the prescriptive norms regulating the dramatic text in the early modern age. Without entering the debate on the„ spectrum and transcendence of the cataegories ’acotación’ and ’didascalia’, special attention will be paid to the playwright’s role in the case of one of the most important creators in Spanish Baroque Drama, Félix Tope de Vega Carpió, who was born about 450years ago, in 1562, in order to go into detail about the readers’ complex interactions between production and reception of a written drama and theatricalperformance.